PENGARUH EFEKTIVITAS FULL DAY SCHOOL TERHADAP PEMBENTUKAN KARAKTER SISWA DI SD MUHAMMADIYAH 23 MEDAN - Nurhaliza, Siti; Rapita Silalahi, Beta; Lestari, Nila; Mujid, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of the effectiveness of the Full Day School system on character formation among students at SD Muhammadiyah 23 Medan. The increasing moral degradation and juvenile delinquency in society have prompted the implementation of Full Day School as a solution to reinforce students’ character by extending school hours to 9-10 hours daily. The purpose of this research is to evaluate the contribution of Full Day School effectiveness in shaping student character. Employing a quantitative approach with simple linear regression analysis, data were collected through validated questionnaires from a sample of 170 students. The results show a significant positive effect of Full Day School effectiveness on character formation, with a regression coefficient of 2.390 and a determination coefficient (R²) of 0.646, indicating that 64.6% of the variance in character development can be explained by the Full Day School system. Thus, Full Day School plays a crucial role in fostering values such as discipline, honesty, religiosity, tolerance, and social cooperation. The study indicates the necessity of support from both school and family environments to optimize character education. These findings offer practical insights for educational institutions aiming to improve students’ moral development through extended learning hours and structured activities.